Strategies for feeding the world more sustainably with organic agriculture - Adrian Muller (Nature Portfolio, 2017)
Organic agriculture requires fewer inputs but produces lower yields than conventional farming. Here, via a modeling approach, Muller et al. predict that if food waste and meat consumption are reduced, organic agriculture could feed the world without requiring cropland expansion.